Interlanguage in Error Analysis Study - Basturi Hasan (Aksara: Jurnal Bahasa dan Sastra, 2015)
Inter-language theory is naturally a constantly evolving theory, having changed considerably since its initial formulation. It is, therefore, not an easy task to produce an accurate account of the theory. The aim of this article is basically to provide a brief and composite account of the inter-language theory. In so doing, some crucial issues are accordingly viewed: (1) error analysis, (2) stages of inter-language development, (3) inter-language transfer, (4) fossilization, (5) input hypothesis, (6) and pidginization as well. There is in fact considerable disagreement about how best to characterize the nature of an inter-language system. Nevertheless, this principle is able to account for insights provided by form-function analysis. Key words: interlanguage, input hypothesis, fossilization, pidginization